User-centred design of a portable fire extinguisher - Amos, Mary; Lawson, Glyn (SAGE, 2017)
This case study documents the process followed to produce an alternative design of fire extinguisher. The work focuses on how informative data can be gathered for an ethically challenging product scenario through the use of a range of user-centred research methods, including: literature review; product evaluation; shadowing study; empathy study; expert interview; focus groups; and simulation equipment. Design improvements as a consequence of this process include: reductions in size and weight; refillable cartridges; single-handed operation; intuitive form; minimal clean up post-use; and better portability.